Takhrij Hadis Manual Hadis Seekor Anjing dan Kisah Pelacur yang Masuk Surga - Umu Solikhah; Muhammad Alif (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
Water alms are one way to get forgiveness from Allah SWT and get heaven. There is a hadith that discusses the virtue of giving drink to animals. This shows that Islam teaches to do good to every creature, including animals. Among the hadiths that are raised is the discussion of an adulterer who gave a dog a drink, and finally he got forgiveness of sins. One thing to note is no matter how bad your past is, no matter how big the sins you have made, do not despair and feel very low, believe that Allah's forgiveness is real, open, Promise to repent and cover up his actions with good deeds and sincerity in carrying them out.